The burden, risk factors and unique etiologies of stroke in South-East Asia Region (SEAR) - Jeyaraj D. Pandian; Madakasira Vasantha Padma Srivastava; Sanjith Aaron; Udaya K. Ranawaka; Narayanaswamy Venketasubramanian; Ivy Anne Sebastian; Ranjit J. Injety; Dorcas B.C. Gandhi; Nistara S. Chawla; Pranay J. Vijayanand; Sukanya Rangamani; Yogeshwar V. Kalkonde (The Lancet Regional Health - Southeast Asia, 2023)
Summary: The World Health Organization (WHO) South East Asia Region (SEAR) comprises 11 countries, which are one of the most culturally, topographically, and socially diverse areas worldwide, undergoing an epidemiological transition towards non-communicable diseases, including stroke and other cardiovascular diseases (CVDs). This region accounts for over 40% of the global stroke mortality. Few well-designed population-based epidemiological studies on stroke are available from SEAR countries, with considerable variations among them. Ischemic stroke, a common stroke subtype, has higher frequencies of intracerebral hemorrhage in many countries. Along with an aging population, the increased prevalence of risk factors such as hypertension, diabetes mellitus, tobacco and alcohol consumption, lack of physical activity, high ambient pollution, heat, and humidity contribute to the high burden of stroke in this region. SEAR's many unique and uncommon stroke etiologies include cerebral venous thrombosis, tuberculosis, dengue, scrub typhus, falciparum malaria, snake bite, scorpion sting, etc. Current data on stroke burden and risk factors is lacking, compelling an urgent need for high-quality hospital-level and population-level data in all SEAR countries. Strategies towards a consolidated approach for implementing improved stroke prevention measures, stroke surveillance, and established stroke systems of care are the path to bridging the gaps in stroke care.